(untitled) (Research, Society and Development, 2021)
This study aims to present an interpretation regarding Stable Unions and Concubinage are very common forms of coexistence that we find in affective relationships conceptualized as parallel or simultaneous families, between two people. However, in these forms of unions that lay people usually understand to be the same type of relationship, in the legal world that accepts these two types of coexistence between two people, they are interpreted as different types of relationships and consequently have different rights. In this sense it is important to clarify the purposes of each one as provided by the law of concubinage that is in art. 1.727 of the CC based on the doctrines and jurisprudence of the state of Rio Grande do Sul. It is an investigative, qualitative bibliographic research and is divided into three parts to better clarify its purposes. The first part talks about the historical aspects of civil law, dedicating itself to thinking about family law in the Civil Code, as well as the understanding of what is the parallel families, in the second part the text is structured to discuss the jurisprudence of the state of Rio Grande do Sul in situations of concubinage and parallel families in the period of 5 (five) years, in the third part it returns to the main aspects of the different decisions of the state courts regarding the proposed theme.